Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So $$f(x)=\frac{x+1}{2x-1}$$ and $$g(x)$$ is an inverse of $$f(x)$$

I have the points on $f(x)$ of (2,1). So I know that $f(2)=1$, $g(1)=2$ and $g'(1)=\frac{1}{f'[g(1)]}$ so $g'(1)=\frac{1}{f'(2)}$ and $f'(x)=\frac{(2x-1)-2(x+1)}{(2x-1)^2}$ so after plugging in 2 in $f'(x)$ I get $\frac{-3}{9} or -\frac{1}{3}$. However, I'm getting the wrong answer and I do not know what I am doing wrong. I have one more attempt at getting the correct answer, so any help would be greatly appreciated. A step by step explanation of what I'm doing wrong would also be greatly appreciated, thanks!

share|improve this question

2 Answers 2

up vote 1 down vote accepted

user99680 made a nice observation, but actually you didn't do anything wrong except an incorrect manipulation. You found $f'(2) = -\frac{1}{3}$, and you want $g'(1) = \frac{1}{f'(2)}$ which would be $-3$.

share|improve this answer

Notice that the function is its own inverse, i.e., $f(f(x))=x$: $$\frac {f(x)+1}{2f(x)-1} = \frac {\frac{x+1}{2x-1}+1}{\frac{2x+2}{4x-2}-1}=\frac{\frac{x+1+2x-1}{2x-1}}{\frac{2x+2-4x+2}{4x-2}}=\frac{\frac{3x}{2x-1}}{\frac{2(3x)}{2(x-1)}}=x$$. Since $f$ is its own inverse, $(f^{-1}(1))'=f'(1)=-3$, since $f'(x)= \frac {-3}{(2x-1)^2}$, as you computed yourself.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.